Cross-Cultural Management in Academic Institutions: A Perspective from Asia and West - Park, Tiwa (Journal of Roi Kaensarn Academi, 2024)
Cross-cultural management in institutions can help students and faculty members promote a learning culture. However, managing multicultural groups can be challenging for higher educational institutions. Therefore, this research aimed to identify the significant cultural differences in communication styles, leadership preferences, and team dynamics between Asian and Western students and faculty. Moreover, it has highlighted how cultural backgrounds influence teaching methods, classroom participation, and student-instructor interactions. Furthermore, the study has determined the challenges and benefits of working in multicultural academic teams. This research is qualitative and focused on literature-based arguments. The data were gathered from literature published in reputed journals. The results highlighted that due to different cultures, the communication styles, leadership preferences, and decision-making abilities of Asian and Western students are different. Therefore, the teaching strategies, learning patterns, and student-faculty relations perceived by each group are different. Western students prefer directness and open debate, but Asian students prefer indirect communication and respect the university policies. Similarly, Western teachers focus on group discussion and active learning. Conversely, Asian teachers rely on structured lectures. This research’s findings can act as guidelines for universities; they can acknowledge cultural differences and implement the recommendations of this study to create a more inclusive learning environment.